Neonatal listeriosis in the UK 2004–2014. Issue 3 (March 2017) - Sapuan, Shari; Kortsalioudaki, Christina; Anthony, Mark; Chang, John; Embleton, Nicholas D.; Geethanath, Ruppa M.; Gray, Jim; Greenough, Anne; Lal, Mithilesh K.; Luck, Suzanne; Pattnayak, Santosh; Reynolds, Peter; et al.
Summary: Objective: To define the clinical features and outcomes of neonatal listeriosis, and identify the maternal risk factors to seek scope for improvement. Methods: Neonatal listeriosis was identified prospectively from a United Kingdom neonatal infection surveillance network (neonIN) between 2004 and 2014. The participating neonatal units completed a study-specific proforma. Results: The incidence of neonatal listeriosis was 3.4 per 100, 000 live births. Of the 21 cases identified, 19 were confirmed with a median gestational age of 33 weeks and a median birth weight of 1960 g. The majority had clinical features (95%, 18/19), presented within the first 24 h (95%, 18/19), and received penicillin empirically (94%, 18/19). The neonatal case-fatality rate was 21% (24% if probable cases were included). A proportion of mothers were investigated (60%, 12/18) and diagnosed with listeriosis (58%, 7/12); 32% (6/19) were treated with antibiotics but only 33% (6/12) included penicillin. Discussion: Despite its rarity and the prompt and appropriate use of antibiotics neonatal listeriosis has a high case-fatality rate. There is room for improvement in the adherence to the empiric antibiotic choice for puerperal sepsis, according to the national guidelines as this, would target listeriosis. Strategies should be in place to prevent pregnancy-associated listeriosis in higher risk population. Highlights: Despite its rarity and the prompt and appropriate use of antibiotics neonatal listeriosis has a high case-fatality rate. Better adherence to the national guidance for empiric antibiotics choice in puerperal sepsis would also targets listeriosis. A clearer understanding of risk factors in pregnant women from ethnic minority could improve prevention.